2020
DOI: 10.3390/diagnostics10070470
|View full text |Cite
|
Sign up to set email alerts
|

Azygos Lobe: Prevalence of an Anatomical Variant and Its Recognition among Postgraduate Physicians

Abstract: The right azygos lobe is a rare anatomical variant of the upper lung lobe that can be misdiagnosed as a neoplasm, a lung abscess, or a bulla. The aim of this study was to assess the prevalence of right azygos lobe and to evaluate the ability of postgraduate doctors to correctly identify right azygos lobe. We analyzed a total of 1709 axial thoracic multi-detector computed tomography (CT) images for the presence of an azygos lobe. Additionally, a paper-based survey was distributed among a sample of intern doctor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…The population was not reported in one study (3500 subjects, 0.3%). Gender-based prevalence was calculated from six studies (Al-Mnayyis et al, 2020;C aceres et al, 1993;Clive, 1943;Ichikawa et al, 2008;Özdemir et al, 2016;Rauf et al, 2012), in which 2527and 32,908 were identified as male and female, respectively. Six diagnostic tools were used to detect the AL including X-rays (47 studies), CT (16 studies), dissection (11 studies), surgical identification (seven studies), MRI (five studies), and analysis of preadmission records (one study) (Table 1).…”
Section: Demographical Distributions Of the Subjects And Diagnostic Methodsmentioning
confidence: 99%
“…The population was not reported in one study (3500 subjects, 0.3%). Gender-based prevalence was calculated from six studies (Al-Mnayyis et al, 2020;C aceres et al, 1993;Clive, 1943;Ichikawa et al, 2008;Özdemir et al, 2016;Rauf et al, 2012), in which 2527and 32,908 were identified as male and female, respectively. Six diagnostic tools were used to detect the AL including X-rays (47 studies), CT (16 studies), dissection (11 studies), surgical identification (seven studies), MRI (five studies), and analysis of preadmission records (one study) (Table 1).…”
Section: Demographical Distributions Of the Subjects And Diagnostic Methodsmentioning
confidence: 99%
“…In this study, the prevalence was found to be 1.39% in women and 1.64% in men. In the study conducted by Al-Mnayyis et al with 1709 CT scans, the prevalence of the azygos lobe was found to be 1.01%, 0.62%, and 0.88% in men, women, and all cases, respectively [13]. In the study conducted by Perincek et al, the frequency of azygos lobes was found to be 1.09%, and the incidence was found to be higher in men than in women (approximately 56% and 44%, respectively) [8].…”
Section: Discussionmentioning
confidence: 91%
“…The azygos lobe is a rare anatomical variant seen in the upper lobe of right lung [1,2]. It is typically seen in the medial portion of the upper lobe of right lung [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The azygos lobe is a rare anatomical variant seen in the upper lobe of right lung [1,2]. It is typically seen in the medial portion of the upper lobe of right lung [1][2][3]. It is separated from the rest of the right upper lobe by an accessory fissure, known as the azygos fissure [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation